2013
DOI: 10.1107/s0907444913017575
|View full text |Cite
|
Sign up to set email alerts
|

Cross-protomer interaction with the photoactive site in oligomeric proteorhodopsin complexes

Abstract: Proteorhodopsins (PRs), members of the microbial rhodopsin superfamily of seven-transmembrane-helix proteins that use retinal chromophores, comprise the largest subfamily of rhodopsins, yet very little structural information is available. PRs are ubiquitous throughout the biosphere and their genes have been sequenced in numerous species of bacteria. They have been shown to exhibit ion-pumping activity like their archaeal homolog bacteriorhodopsin (BR). Here, the first crystal structure of a proteorhodopsin, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
213
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(218 citation statements)
references
References 41 publications
5
213
0
Order By: Relevance
“…3A); in contrast, it is suggested that KR2 forms pentamers (Fig. 3B), and PRs assemble into pentamers or hexamers [32,[38][39][40] (Fig. 3C).…”
Section: Structure-function Relationships Of Br Hr and Narmentioning
confidence: 99%
See 1 more Smart Citation
“…3A); in contrast, it is suggested that KR2 forms pentamers (Fig. 3B), and PRs assemble into pentamers or hexamers [32,[38][39][40] (Fig. 3C).…”
Section: Structure-function Relationships Of Br Hr and Narmentioning
confidence: 99%
“…3). In some cases, lipid molecules or ions mediate the interaction between monomers, and stabilize the oligomer [32,36,38] (Fig. 3A and B).…”
Section: Structure-function Relationships Of Br Hr and Narmentioning
confidence: 99%
“…The discovery of PR demonstrated the power of metagenomics, especially when combined with subsequent hypothesis testing at the physiological or biochemical level (in this case, experiments with heterologously expressed PR validated its retinal binding and light-driven proton-pumping activities [28]). The biochemistry and photobiology of this protein have also been studied in detail (29), and a blue-tuned PR variant (Med12BPR) was the first for which the crystal structure was determined (30).…”
mentioning
confidence: 99%
“…In addition to other retinal proteins found early in archaea, such as halorhodopsins and sensory rhodopsins, recent studies have demonstrated the presence of a number of proteins belonging to MR family in a wide range of organisms 5, 6 . Crystal structures obtained for some of these proteins have shown that the arrangement of the seven helices is conserved 7, 8 , and their 7TM domains are valuable for examinations of the effects of experimental conditions and sequence variation on structure.…”
Section: Introductionmentioning
confidence: 99%